The Current State of Handovers. Issue 1 (June 2016) - Abraham, Joanna; Patterson, Emily; Riesenberg, Lee Ann; Wears, Robert
The paper presents the varying perspectives on the current state of handoff research and practice. Informed by their research studies, the interdisciplinary expert panel discussed in-situ experiences with respect to the good, the bad and the ugly of handoffs in hospitals. Furthermore, the panelists highlighted the need for: (a) collaborative and interdisciplinary research on handoffs with researchers and practitioners from computer sciences, communication, linguistics, human factors etc., and (2) extra-mural funding to conduct large-scale handoff evaluation studies.